Robert Morris's folly : the architectural and financial failures of an American founder - Smith, Ryan K. (Lewis Walpole series in eighteenth-century culture and history., 2014)
In 1798 Robert Morris - 'financier of the American Revolution', confidant of George Washington, former U.S. senator - plunged from the peaks of wealth and prestige into debtors'prison and public contempt. How could one of the richest men in the United States, one of only two founders who signed the Declaration of Independence, the Articles of Confederation, and the Constitution, suffer such a downfall? This book examines for the first time the extravagant Philadelphia town house Robert Morris built and its role in bringing about his ruin.